Claiming the future : choosing prosperity in the middle east and north africa - Shafik, Nemat; World Bank. (Washington, D.C. : The World Bank, 1995)
The countries of the Middle East and North Africa (MENA) region face unprecedented challenges. The pace of change in the global economy has been faster, prompting the need for new economic strategies to participate successfully in it. Meanwhile, the end of the cold war, the aftermath of the Gulf conflict, the evolving Middle East peace process, and the rise of fundamentalism call into question traditional political assumptions and structures. Navigating these turbulent waters requires a coherent and purposeful vision of the way ahead among the region's leaders, business people, and citizens. This study is intended to contribute to such a vision. It is the product of considerable work at the World Bank on long-term issues in the Middle East and North Africa. The troubling and surprising aspects of the findings lie in the region's poor economic performance during the past decade. The explanation lies in the region's policies and in the dramatic recent changes in the international economic environment. The study offers cause for hope as well. Indeed, many MENA countries have clearly demonstrated that they can dramatically reduce poverty, educate unprecedentedly large numbers of their citizens, and accumulate substantial capital assets. The region's economic future lies in making productive use of these resources - human, financial, and physical - to take advantage of the opportunities that globalization brings. In addition, the well-being of all MENA's people will depend on realizing a development paradigm of growth that is rapid, widely shared throughout societies, and environmentally sustainable. This study focuses on the "rapid" and "shared" components of the paradigm. -- Publisher description
"This report was prepared by a team led by Nemat Shafik ... "--p. iv.
Includes bibliographical references (p. 83-88).
rpm 01/09/16
Loans
Keywords: Middle East -- Economic policy; Middle East -- Economic conditions; Africa, North -- Economic policy; Africa, North -- Economic conditions; Economic history; Economic policy; Middle East; Africa, North